Soil degradation: a threat to developing-country food security by 2020? - Scherr, Sara J. (International Food Policy Research Institute, 1999)
Global population in the year 2020 will be a third higher than in 1995, but demand for food and fiber will rise by an even higher proportion, as incomes grow, diets diversify, and urbanization accelerates. However this demand is met, population and farming pressure on land resources will intensify greatly. There is growing concern in some quarters that a decline in long-term soil productivity is already seriously limiting food production in the developing world, and that the problem is getting worse. Sarah Sherr first focuses on the magnitude and effects of soil degradation. She then addresses soil degradation in the future and ends her brief with policy and research priorities.